2016
DOI: 10.1063/1.4944514
|View full text |Cite
|
Sign up to set email alerts
|

Copper dusting effects on perpendicular magnetic anisotropy in Pt/Co/Pt tri-layers

Abstract: The effect of Cu dusting on perpendicular magnetic anisotropy of sputter grown Pt/Co/Pt stack in which the Cu layer is in proximity with that of Co is investigated in this work. We used magneto optic Kerr effect microscopy measurements to study the variation in the reversal mechanisms in films with Co thicknesses below 0.8nm by systematically varying their perpendicular magnetic anisotropy using controlled Cu dusting. Cu dusting was done separately above and below the cobalt layer in order to understand the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Figure 7 a shows and the corresponding vs , for various . Here, 3 < < 7.5 10 5 J/m 3 , which are in general agreement with studies of comparable Co and Pt thicknesses, using different refractory metal seed layers (such as Ru and Ta) 61 , 67 , 68 . No clear dependence of on and is found, which can most likely be attributed to the limited range of and values explored.…”
Section: Resultssupporting
confidence: 88%
“…Figure 7 a shows and the corresponding vs , for various . Here, 3 < < 7.5 10 5 J/m 3 , which are in general agreement with studies of comparable Co and Pt thicknesses, using different refractory metal seed layers (such as Ru and Ta) 61 , 67 , 68 . No clear dependence of on and is found, which can most likely be attributed to the limited range of and values explored.…”
Section: Resultssupporting
confidence: 88%
“…Using a toy model bearing semblance to that used by Bruno to explain RKKY-like interlayer exchange coupling in GMR stacks, [47] has shown that if this layer is also conducting, then it can suppress iDMI due to its screening effect. Similar reports of suppressed iDMI and K eff upon addition of metallic spacer layers have been reported [44,47,49,50]. Furthermore, the intermixing effect, understood within the real space spin-spiral based DMI model [37], can microscopically alter the hybridization of 3d-5d bands around the Fermi level in a complicated way.…”
Section: Resultssupporting
confidence: 73%
“…The iDMI value is one of the highest in Pt/Co systems, which are also characterized by strong perpendicular magnetic anisotropy (PMA). Thus, many of the iDMI systems are basing on Pt/Co ultrathin films with broken inversion symmetry, e.g., Pt/Co/AlO x [8,9], Pt/Co/MgO [10] Pt/Co/Ta [11], Pt/Co/(W,Ta,Pd) [12], Pt/Co-Ni/Ta [13], Ir/Fe/Co/Pt [14], Pt/Co/Cu/AlO x [15], Pt/Co/Os/Pt [16], Pt/Cu/Co/Pt [17]. In Ref.…”
Section: Introductionmentioning
confidence: 99%